Web-Based Digital Administration Service System for Nossa Senhora Do Rosario Parish, Oé-Cusse - Jaime Da C.L. Soares; Luciana Aurelia; Marcelino da Silva; Jose Venancio Da C. Freitas; Constantino F.Seisa (Jurnal Impresi Indonesia, 2026)
The Parish Church of Nossa Senhora do Rosário, located in the Special Administrative Region of Oecusse-Ambeno, Timor-Leste, plays a vital role in providing spiritual and administrative services to the local Catholic community. Traditionally, church administration—including the recording of sacramental and administrative documents such as Baptism, First Communion, Confirmation, Marriage, recommendation letters, and ordination certificates—has been conducted manually. These conventional methods often result in operational inefficiencies, service delays, data inaccuracies, and limited transparency. This study was conducted in the Pante Macassar subdistrict, specifically in Costa Village, the central hub of the local Catholic community. The primary objective is to develop a web-based church administration system using PHP and MySQL, employing the Rapid Application Development (RAD) methodology to ensure an iterative and user-responsive process. The implementation demonstrates significant improvements in administrative efficiency, data consistency, and the ease of managing sacramental records while enhancing the parish’s internal operational transparency. This study contributes both practically and academically to the digital transformation of religious institutions, particularly for the Parish of Nossa Senhora do Rosário.